Factors Controlling Carbon Metabolism and Humification in Different Soil Agroecosystems - S. Doni; C. Macci; E. Peruzzi; B. Ceccanti; G. Masciandaro (The Scientific World Journal)
The aim of this study was to describe the processes that control humic carbon sequestration in soil. Three experimental sites differing in terms of management system and climate were selected: (i) Abanilla-Spain, soil treated with municipal solid wastes in Mediterranean semiarid climate; (ii) Puch-Germany, soil under intensive tillage and conventional agriculture in continental climate; and (iii) Alberese-Italy, soil under organic and conventional agriculture in Mediterranean subarid climate. The chemical-structural and biochemical soil properties at the initial sampling time and one year later were evaluated. The soils under organic (Alberese, soil cultivated with Triticum durum Desf.) and nonintensive management practices (Puch, soil cultivated with Triticum aestivum L. and Avena sativa L.) showed higher enzymatically active humic carbon, total organic carbon, humification index (B/E3s), and metabolic potential (dehydrogenase activity/water soluble carbon) if compared with conventional agriculture and plough-based tillage, respectively. In Abanilla, the application of municipal solid wastes stimulated the specific β-glucosidase activity (extracellular β-glucosidase activity/extractable humic carbon) and promoted the increase of humic substances with respect to untreated soil. The evolution of the chemical and biochemical status of the soils along a climatic gradient suggested that the adoption of certain management practices could be very promising in increasing SOC sequestration potential.